Evaluation of Root Growth Dynamics and Yield Components of Quinoa (Chenopodium quinoa) Cultivars by Changing Phosphorus and Zinc Levels - Anise Jorfi; Mojtaba Alavifazel; Abdolali Gilani; Mohammad Reza Ardakani; Shahram Lack (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
Proper distribution of plant root facilitates the uptake of nutrients and improves crop yields. This study aims to evaluate the root and shoot structure of quinoa cultivars in response to the application of phosphorus and zinc in the Research, Agricultural Education and Natural Resources Center of Khuzestan province in a factorial design with three factors including the use of triple superphosphate fertilizer at four levels (0, 6, 12, 18 mg.kg-1 soil weight), foliar application of zinc sulfate in three amounts (water without zinc sulfate (control), foliar application at 4 and 8 per thousand concentrations) and three quinoa cultivars (Giza 1, Q26, Titicaca) were performed in pot and in three replications. The results showed that root parameters such as root dry weight, root width, root diameter, distance from the first branch to the tip root, and the weight ratio of root to shoot were affected by phosphorus fertilizer levels and quinoa cultivars (P≤0.01) and foliar application of zinc sulfate had a significant effect only on root dry weight, root width, distance from the first branch to the root tip, root density, root weight to shoot weight, and aerial part parameters. Q26 cultivar was identified as the best cultivar in terms of root structure development, which at 18 mg.kg-1 phosphorus levels and 4 per thousand zinc sulfate concentration had a maximum root dry weight (3.23 g.plant-1), root width (18.06 cm) and distance from the first branch to the root tip (53.23). At these levels of element consumption, the highest number of grains per plant (4542) were obtained in cultivar Q26. Based on the experiment results, the optimal level of elements by reducing antagonistic effects and increasing synergistic effects of P and ZnSO4 led to the root structure development, improved element uptake and increased production components of quinoa cultivars.